Mengoptimalkan Kreativitas Tim: Peran Resiliensi dalam Memediasi Gaya Kepemimpinan dan Stabilitas Anggota di Organisasi Kemahasiswaan - Theofilus Christ Marvellianto; Syarif Hidayatullah; Umu Khouroh (Sekolah Tinggi Ilmu Manajemen Indonesia (STIMI) Banjarmasin, 2026)
In the current era of globalization, higher education institutions play a vital role as one of the providers of human resources who can adapt and are competent for the needs of the global job market. To meet the demands of the global workforce today, students need not only theoretical or hard skills but also a balanced development of soft skills, one of which can be achieved through student organizations. The purpose of this research is to analyze the role of transformational leadership, shared leadership, and membership stability on team creativity through team resiliency. This study aims to explain how team resiliency mediates the relationship between these three variables and team creativity. The research method used in this study is quantitative, with a sample of 205 members of the student organization at BINUS Malang campus. Data were collected through a Likert scale-based questionnaire, and data analysis was conducted using SEM PLS 3.0. The analysis results show that the direct influence of these three variables has a significant impact on team resiliency, and among the three variables, only transformational leadership does not have a significant direct impact on team creativity. Additionally, the indirect relationship between shared leadership and membership stability on team creativity through team resiliency is significant, while the indirect relationship between transformational leadership and team creativity through team resiliency is not significant. This indicates that the transformational leadership style, which focuses on providing inspiration. Motivating and directing its members has not yet been well received to enhance the creativity of the organization's members and improve team creativity within the organization. These findings are expected to contribute to the chairperson of the BINUS Malang student organization in developing an effective leadership style in fulfilling their role as the chairperson and achieving the organization's goals together